The mechanism of inhibition of Ran-dependent nuclear transport by cellular ATP depletion - Schwoebel, Eric D. (The Rockefeller University Press, 2002)
Rran-dependent nuclear transport requires a nuclear pool of RanGTP both for the assembly of export complexes and the disassembly of import complexes. Accordingly, in order for these processes to proceed, Ran-dependent nuclear import and export assays in vitro require the addition of GTP to produce RanGTP. Notably, no ATP requirement can be detected for these transport processes in vitro. But in vivo, when cells are depleted of ATP by the addition of sodium azide and 2-deoxyglucose to block ATP production by oxidative phosphorylation and glycolysis, respectively, Ran-dependent nuclear import and export are rapidly inhibited. This raised the question of whether there is an ATP requirement for these nuclear transport pathways in an intact cell that has remained undetected in vitro. Here we report that the free (but not total) GTP concentration rapidly drops to an undetectable level upon ATP depletion as does the availability of RanGTP. Our conclusion is that the inhibition of Ran-dependent nuclear transport observed upon ATP depletion in vivo results from a shortage of RanGTP rather than the inhibition of some ATP-dependent process.